2018
DOI: 10.1038/s41598-018-28359-0
|View full text |Cite
|
Sign up to set email alerts
|

Coherent backscattering in quasi-ballistic ultra-high mobility GaAs/AlGaAs 2DES

Abstract: A small and narrow negative-magnetoresistance (MR) effect that appears about null magnetic field over the interval −0.025 ≤ B ≤ 0.025 T in magnetotransport studies of the GaAs/AlGaAs 2D system with μ ≈ 107cm2/Vs is experimentally examined as a function of the sample temperature, T. The temperature dependent magnetoresistance data were fit using the Hikami et al. theory, without including the spin-orbit correction, to extract the inelastic length, li, which decreases rapidly with increasing temperature. It turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 95 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…The experimental data were fit using the Hikami 2D WL theory 64 , neglecting the spin orbit scattering term, and also electron-electron interaction effects. Our previous reports reveal the absence of electron-electron interaction effect in these specimens 57,65 . In the presence of spin-orbit interaction one would expect a positive magnetoresistance in these types of device structures, rather than a negative magnetoresistance 51,66 .…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The experimental data were fit using the Hikami 2D WL theory 64 , neglecting the spin orbit scattering term, and also electron-electron interaction effects. Our previous reports reveal the absence of electron-electron interaction effect in these specimens 57,65 . In the presence of spin-orbit interaction one would expect a positive magnetoresistance in these types of device structures, rather than a negative magnetoresistance 51,66 .…”
Section: Discussionmentioning
confidence: 54%
“…We have previously reported the effect of bath temperature on the inelastic scattering length 65 , where the measurements were taken under dark conditions, i.e. without microwaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the dark magnetoresistance properties of high mobility GaAs/AlGaAs 2DES are concerned, our previous reports exhibit two distinct dark MR effects, which are: 1) negative Giant Magnetoresistance (negative‐GMR) effect and 2) narrow negative MR effect around B = 0 T. Experimental studies have shown that the negative‐MR effect around zero magnetic fields is temperature dependent (i.e., T ≥ 1 K) . However, another study reported a temperature (i.e., T ≤ 800 mK) invariance of the narrow negative magnetoresistance effect .…”
Section: Introductionmentioning
confidence: 91%
“…Low temperature transport studies of high mobility ( μ ≥10 7 cm 2 V −1 s −1 GaAs/AlGaAs two‐dimensional electron systems (2DES) grown by molecular beam epitaxy (MBE) have shown that the transport/elastic scattering length of these device structures can be comparable with the dimensions of the specimens even in the mm scale . Thus, quasi‐ballistic transport is possible in such specimens in the absence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%